Airline traffic forecast and financial trends 2006 to 2008 - International Civil Aviation Organization (Canada : International Civil Aviation Organization, 2007)
This Airline traffic forecast and financial trends 2006 to 2008, analyses trends in airline traffic and financial results over the 1995-2005 period along with factors underlying air traffic demand and presents medium-term global and regional forecasts of scheduled passenger traffic and basic global airline financial trends through to 2008.
System requirements: Adobe Acrobat Reader.
Keywords: Aeronautics, Commercial -- Passenger traffic -- Statistics; Airlines -- Finance -- Statistics